Mediating Role of Emotional Self-Efficacy Between Emotional Intelligence and Creativity: Empirical Study on University Undergraduates - Gürbüz, Fatma Gülruh; Ergun, Hande Sinem; Teraman, Seray Begüm Samur (My University, 2016)
Today’s world requires a professional working life in which there are individuals equipped with different skills, and using composition of those skills. Thus, in modern era, person-job fit, difficulties individual faces in the job and the overall process during their career paths have become important phenomena. In this process, some of the factors make positive contributions to people’ both personal and professional life. In this study, among those factors, Emotional Intelligence, Creativity from both potential and practice perspective and Emotional Self Efficacy have been investigated. The main objective of this study is to unravel the stated untapped relation/pathway between Emotional Intelligence and Creativity in educational context/in University subject domain. In this respect, mediating role of Emotional Self Efficacy in explaining Potential and Practiced Creativity has been mentioned. Data for this study was collected from a sample of 265 students receiving education both from State and Private Universities located in Istanbul. Snowball sampling was applied in order to reach as much students as possible. The data were analyzed by using the Statistical Package for the Social Sciences (SPSS) 21.0 software. Firstly Factor and Reliability Analyses of all measurement instruments were conducted and their factor structure was revised based on the results. Then hierarchical regression analysis was done in order to test the mediating effects. The results show that, Emotional Self Efficacy mediates the effects of Adaptability on only Creative Potential for students. In other words, individuals who; have problem solving ability, are flexible and realistic can have a potential for being creative. When they have a belief in their capability of perceiving emotions in self and the others, using emotions to facilitate thought, understanding emotions and emotional knowledge in the self and the others and regulating emotions in the self and the others (Mayer, Salovey and Caruso, 2004 cf. Kirk, Schutte and Hine, 2008) effect of adaptable abilities lost its effect in explaining their creative potential.
Keywords: Emotional Intelligence; Creative Potential; Practiced Creativity; Emotional Self-Efficacy